Design of E-Module Practicum En-Route Flight Information (EFI) Course with the Rapid Application Development (RAD) Model at Aviation Polytechnic of Surabaya - Saamena, Tirza; Silk Moonlight, Lady; Irfansyah, Ade (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
En-Route Flight Information (EFI) is one of the courses in the Diploma 3 Aeronautical Communication Study Program which studies the procedures for guiding aircraft in class G airspace. Based on Annex 11 Air Traffic Service, class G airspace provides flight traffic services for IFR and VFR flights, where the services provided are Flight Information Service and Emergency Service (Alerting Service) [1]. Flight Information Service is a service performed by providing news and information that is useful and beneficial for safety, security and efficiency for flights. Alerting Service is a service performed by notifying the appropriate relevant agencies, regarding aircraft that require the help of search and rescue units and assisting these agencies, if needed. This research uses the Research and Development method with the Rapid Application Development (RAD) Model with qualitative data analysis techniques and written Interview testing techniques with Material Experts and Media Experts using questionnaires. The objectives of this research are 1) To design an E-Module Design product En-Route Flight Information (EFI) with the Rapid Application Development (RAD) Model at the Aviation Polytechnic of Surabaya which can be used as learning on the Learning Management System (LMS) at the Aviation Polytechnic of Surabaya. The result of this research is a learning using E-Module Practicum En-Route Flight Information (EFI) in the form of flipbooks and mastery tests and discussions equipped with video and audio images that have been adjusted to the “Rencana Pembelajaran Semester” (RPS). Then the final result of an E-Module Practicum En-Route Flight Information (EFI) is implemented on the Learning Management System (LMS) of the Aviation Polytechnic of Surabaya.